Oral Health Status and Practice among Buddhist Monk and Nun Students: Monastery Based Study in Nepal - Prajapati, Dilip; Lama, Sonam Rinchen; Mahanta, Swagat; Subedi, Shreya; Mahat, Swastika (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Introduction: Oral health conditions can be largely preventable but still major health burden for many countries.Objective: The aim of this study was to evaluate oral health status and practice among Buddhist monk and Nun students in Nepal.Methods: Monastery based cross sectional study was performed among 422 students from six monasteries with age group 6 to 20 years old from March to October 2021. A set of oral health related questionnaire were used followed by intraoral examinations including assessment of Decayed Missing Filled Teeth (DMFT), Gingival Status and Calculus Score along with dietary habits. Statistical analysis was performed in SPSS with descriptive, Mann Whitney test and Spearman’s correlation test.Results: Oral health knowledge attitude and practice were good in compared to other school children with same age groups. The mean DMFT Score were 1.62 ± 2.19 and mean dmft 0.59 ± 1.4 with good gingival and calculus score. Very few of them (47, 11.1%) had filled permanent tooth and 98 (23.2%) of them had dental pain within past six months of study. None of them (100%) had undergone orthodontic treatment where 23% had class III Angle’s Molar relationship. Dental caries showed an increasing trend in relation to age with significant moderate correlation (r=0.35, p